Neonatal Duodenal Obstruction in Situs Inversus: Surgical Implications of a Pre-Duodenal Portal Vein (Journal of Paediatric Surgeons of Bangladesh, 2026)
Background: Pre-duodenal portal vein (PDPV) is a rare congenital vascular anomaly resulting from abnormal embryological development of the vitelline venous system. Although often asymptomatic, PDPV may be associated with duodenal obstruction, particularly in neonates with additional congenital anomalies such as situs inversus, intestinal malrotation, and duodenal atresia.Case Presentation: We report a four-day-old male neonate presenting with bilious vomiting and features of proximal intestinal obstruction. Imaging revealed duodenal obstruction with situs inversus abdominus. Laparotomy demonstrated a pre-duodenal portal vein crossing the second part of the duodenum with an associated intraluminal duodenal membrane. Membrane excision and gastro-duodenostomy were performed to bypass the obstruction while avoiding injury to the anomalous portal vein. The postoperative recovery was uneventful.Conclusion: The coexistence of PDPV, duodenal obstruction, and situs inversus is exceedingly rare. Intraoperative recognition of anomalous vascular anatomy and tailored surgical planning are critical to prevent catastrophic vascular injury and ensure favorable outcomes.Journal of Paediatric Surgeons of Bangladesh (2022) Vol. 13 (1 & 2): 49-51